Load and fatigue monitoring in the Australian Football League: A practical example - Cormack, S. (7th World Congress on Science and Football (WCSF), 2011, 2011)
Australian Football (AF) is a contact team sport lasting over 100 min, requiring players to cover in excess of 12 km per match at an average of approximately 128 meters per minute, in addition to a large number of repeated high intensity efforts. Challenging within match performance requirements are superimposed on a regular season lasting 22 rounds, with generally one match played per week, followed by a 4 week finals series. Given the requirement to win enough matches during the regular season in order to qualify for the finals series, and strict limitations on the number of players available for selection, it is important for Australian Football League clubs to utilise effective monitoring systems to optimise the physical response of players to regular match play. The aim of such a system is to avoid undue fatigue and potentially assist in preventing injury. The system of load management and fatigue monitoring in use at Essendon Football Club has been developed using numerous valid and reliable tools in a "mixed methods" approach to assess the status of athletes and drive manipulation of the training process on an individual basis. The system comprises measures of the training and competition load along with the use of valid and reliable objective markers and subjective self reporting tools combined with statistical analysis on both acute and chronic timelines. Some examples of the assessment tools in place include an Athlete Distress Questionnaire, Neuromuscular Fatigue, Hormonal Status and Rating of Perceived Exertion4. Whilst none of the tools utilised can be considered to be the definitive marker of the fatigue response in elite AF, their use in combination provides useful information about the status of each athlete that can be used to manipulate training loads.